AMBIVALENSI JIHAD DAN TERORISME: TINJAUAN ANALISIS SEMANTIK-KONTEKSTUAL AYAT-AYAT JIHAD - Khairun Nisa; Annas Rolli Muchlisin (Pascasarjana UIN ANTASARI Banjarmasin, 2018)
In the early 21st century, the global world had an extreme fright after WTC (World Trade Centre) was attacked by international terrorist networks in the name of Islam. These actions disgrace the name of Islam in international world which cause Islamopobhia in most countries. These acts of terrors inspire other terrors. Indonesia was also not free from terror attacks. One of these was the Bali attack in 2012 carried out by three jihadist called